Clinical Outcomes of BCMA CAR-T Cells in a Multiple Myeloma Patient With Central Nervous System Invasion - Wang, Ting; He, Ting; Ma, Lie; Yang, Yazi; Feng, Ru; Ding, Yanping; Shan, Yueming; Bu, Bing; Qi, Feifei; Wu, Fei; Lu, Xin-an; Liu, Hui (Frontiers in Oncology, 2022)
Background Multiple myeloma (MM) is the second most common hematological malignancy that still lacks effective clinical treatments. In particular, MM with central nervous system (CNS) invasion occurs rarely. Although B-cell maturation antigen (BCMA)-targeted chimeric antigen receptor-T (CAR-T) cell therapy has shown great promise for the treatment of relapsed/refractory MM, few studies have reported whether BCMA CAR-T could inhibit MM with CNS invasion. Case Presentation In this study, we report a special case of a 63-year-old male patient who suffered MM with CNS invasion and presented rapid extramedullary disease (EMD) progression into multiple organs. Before CAR-T cell infusion, this patient received five cycles of bortezomib, Adriamycin, and dexamethasone (PAD) and an autologous transplant as the front-line treatment, followed by two cycles of bortezomib, lenalidomide, and dexamethasone (VRD) as the second-line regimen, and daratumumab, bortezomib, dexamethasone (DVD) as the third-line regimen. Since the patient still showed rapid progressive disease (PD), BCMA CAR-T cells were infused, and 1 month later, a stringent complete response (sCR) was achieved, and the response lasted for 4 months. Meanwhile, only grade 1 cytokine release syndrome (CRS) was observed. Conclusion This case report demonstrated that BCMA CAR-T could effectively eradicate CNS-involved MM with low adverse events, suggesting that CAR-T cell therapy could be a feasible therapeutic option for this kind of refractory disease. Clinical Trial Registration https://ClinicalTrials.gov, identifier: NCT04537442.a